Dimensional Stability and Accuracy of Silicone Impression Materials after Ozone Water Disinfection: An In Vitro Study - Abinaya . Kutralanathan; Ahila . Singaravel Chidambaranathan; Muthukumar . Balasubramaniam (Frontiers in Dentistry)
Objectives: This study evaluated the effect of ozone water disinfection on dimensional stability and accuracy of silicone impression materials.